Early diagnosis and complications of Acute Ischemic Stroke - Marto, João Pedro (2024)
Abstract Stroke is the first cause of death and disability in Portugal, and the second cause of death and third cause of disability worldwide. In patients with stroke, treatment interventions are time-dependent, meaning that shorter time from stroke onset to treatment is associated with better outcomes. Blood-based biomarkers represent a potential alternative to neuroimaging for early and rapid stroke diagnosis. Accurate and timely differentiation between patients with acute ischemic stroke (AIS), intracerebral hemorrhage (ICH) and stroke mimics (SM) could improve prehospital pathways and potentially allow earlier treatment administration. We conducted an exploratory prospective observational study on untargeted blood biomarkers in consecutive patients with suspected stroke, collecting blood samples at hospital admission. Quantitative analysis from mass spectrometry data was performed and biomarker-based prediction models were developed to differentiate AIS from ICH and from ICH and SM. Biomarker-based prediction models including intercellular adhesion molecule-2, plasminogen like-A, complement component 3, syntaxin binding protein-5 and immunoglobulin heavy variable 3-64 showed between 75 to 88% sensitivity at 100% specificity for identifying patients with AIS. In addition to the timing of diagnosis and treatment, early stroke recurrences influence long-term prognosis. Stroke patients ideally are hospitalized in stroke units in order to prevent stroke recurrence and other in-hospital complications. However, the impact of being in a stroke unit at the time of an early recurrent stroke has not previously been studied. In a retrospective analysis, we showed that in patients with an in-stroke unit stroke, the exact time of stroke onset was more frequently known than in other stroke patients, that treatment opportunities were less often missed than in other patients with in-hospital stroke, and that the endovascular treatment rate was higher than in patients with community-onset stroke. Finally, patients with in-stroke unit stroke had better functional outcomes than those with other in-hospital strokes or community-onset strokes. Another complication in patients with AIS is early worsening of arterial patency, either due to stroke recurrence or progressive clot formation. However, no study so far has described the frequency, associated factors and outcome of patients with worsening of arterial patency. We conducted a retrospective study showing that 3% of patients with AIS experienced worsening of arterial patency within the first 24 hours (with or without preceding revascularisation treatment). History of hypertension, initial stroke severity, intracranial and extracranial stenosis, and good collaterals were identified as independent predictors, and worsening of arterial patency was associated with a six-fold higher likelihood of poorer functional outcome. In patients undergoing endovascular treatment (EVT), reocclusion after initial successful recanalization is another possible complication. This phenomenon has only seldom been studied. In our retrospective study, we showed that 6.6% of patients experienced reocclusion after successful EVT. Preadmission statin therapy, intracranial internal carotid artery occlusion, number of passes during EVT, transient reocclusion during EVT, and atherosclerotic stroke etiology were identified as independent predictors, and its occurrence was associated with a five times higher rate of unfavorable functional outcome. Using a combination of translational and clinical research, this PhD thesis attempts to add new data to reduce the global burden of stroke. We explored a new blood-based biomarker strategy for stroke diagnosis, investigated the protective role of stroke units on early stroke recurrence, and studied predictors and outcome of patients with worsening of arterial patency and reocclusion after EVT. The final discussion of this thesis integrates the potential applications of the results and proposes future research questions.